2020
DOI: 10.31025/2611-4135/2020.13899
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Biological Treatment Plant Sludge to Organic Fertilizer for Applications in Organic Farming

Abstract: Conversion of the sludge generated in the biological treatment plants of glove dipping industries of Sri Lanka to a valuable organic fertilizer after removing toxic metal ions such as heavy metals and excess Zn and Al present in the sludge to allowable limits is described. In order to do so, the raw materials used were analysed for these species and for their nutritional values. Removal of metal ions by different acids such as HNO3 and acetic acid digestion processes are revealed and the results are compared. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, amino acids content in the yeast is an ideal protein source of organic fertilizer because it possesses high content of essential amino acids and fully meeting the nutritional standard. Previously, the proteins recovered from ES without strain addition could be considered as organic fertilizer 48 . However, proteins in this study need more tests to prove that they can meet the safety standards before they can be used in more fields.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, amino acids content in the yeast is an ideal protein source of organic fertilizer because it possesses high content of essential amino acids and fully meeting the nutritional standard. Previously, the proteins recovered from ES without strain addition could be considered as organic fertilizer 48 . However, proteins in this study need more tests to prove that they can meet the safety standards before they can be used in more fields.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, the proteins recovered from ES without strain addition could be considered as organic fertilizer. 48 However, proteins in this study need more tests to prove that they can meet the safety standards before they can be used in more fields. It has been reported that toxic metals, organic pollutants, and microbial toxins are concentrated in sewage sludge through the primary and secondary treatment processes.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations